Matematyka

Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek

Wydawnictwo:Nowa Era

Rok wydania:2015

Wykonaj mnożenie 4.5 gwiazdek na podstawie 6 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

`a)\ (a^2+b)(x-y)=a^2(x-y)+b(x-y)=`  

`\ \ \ =a^2x-a^2y+bx-by` 

 

`b)\ (a-b)(x^2+y^2)=a(x^2+y^2)-b(x^2+y^2)=` 

`\ \ \ =ax^2+ay^2-bx^2-by^2` 

 

`c)\ (-a^2+b)(x^2-y)=`  `-a^2(x^2-y)+b(x^2-y)=` 

`\ \ \ =-a^2x^2+a^2y+bx^2-by` 

 

`d)\ (n^4+2)(m^2+3)=` `n^4(m^2+3)+2(m^2+3)=` 

`\ \ \ =m^2n^4+3n^4+2m^2+6` 

 

`e)\ (n^3-4)(m^3-6)=` `n^3(m^3-6)-4(m^3-6)=` 

`\ \ \ =n^3m^3-6n^3-4m^3+24` 

 

`f)\ (-2n^2+1)(3m^4-2)=` `-2n^2(3m^4-2)+1(3m^4-2)=` 

`\ \ \ =-6m^4n^2+4n^2+3m^4-2` 

 

`g)\ (x^2+3)(a-2b+c)=` `x^2(a-2b+c)+3(a-2b+c)=` 

`\ \ \ =ax^2-2bx^2+cx^2+3a-6b+3c` 

 

`h)\ (y-3)(2a-b^2+4c)=` `y(2a-b^2+4c)-3(2a-b^2+4c)=`   

`\ \ \ =2ay-b^2y+4cy-6a+3b^2-12c` 

 

`i)\ (a^3+b-2c)(x^2-y)=` `(a^3+b-2c)*x^2+(a^3+b-2c)*(-y)=` 

`\ \ \ =a^3x^2+bx^2-2cx^2-a^3y-by+2cy`